Variable ventilation improves pulmonary function and reduces lung damage without increasing bacterial translocation in a rat model of experimental pneumonia. Issue 1 (December 2016) - de Magalhães, Raquel; Samary, Cynthia; Santos, Raquel; de Oliveira, Milena; Rocha, Nazareth; Santos, Cintia; Kitoko, Jamil; Silva, Carlos; Hildebrandt, Caroline; Goncalves-de-Albuquerque, Cassiano; Silva, Adriana; Faria-Neto, Hugo; et al.
Abstract Background Variable ventilation has been shown to improve pulmonary function and reduce lung damage in different models of acute respiratory distress syndrome. Nevertheless, variable ventilation has not been tested during pneumonia. Theoretically, periodic increases in tidal volume (VT ) and airway pressures might worsen the impairment of alveolar barrier function usually seen in pneumonia and could increase bacterial translocation into the bloodstream. We investigated the impact of variable ventilation on lung function and histologic damage, as well as markers of lung inflammation, epithelial and endothelial cell damage, and alveolar stress, and bacterial translocation in experimental pneumonia. Methods Thirty-two Wistar rats were randomly assigned to receive intratracheal ofPseudomonas aeruginosa (PA) or saline (SAL) (n = 16/group). After 24-h, animals were anesthetized and ventilated for 2 h with either conventional volume-controlled (VCV) or variable volume-controlled ventilation (VV), with mean VT = 6 mL/kg, PEEP = 5cmH2 O, and FiO2 = 0.4. During VV, tidal volume varied randomly with a coefficient of variation of 30% and a Gaussian distribution. Additional animals assigned to receive either PA or SAL (n = 8/group) were not ventilated (NV) to serve as controls. Results In both SAL and PA, VV improved oxygenation and lung elastance compared to VCV. In SAL, VV decreased interleukin (IL)-6 expression compared to VCV (median [interquartile range]: 1.3 [0.3–2.3]vs . 5.3 [3.6–7.0];p = 0.02) and increased surfactant protein-D expression compared to NV (2.5 [1.9–3.5]vs . 1.2 [0.8–1.2];p = 0.0005). In PA, compared to VCV, VV reduced perivascular edema (2.5 [2.0–3.75]vs . 6.0 [4.5–6.0];p < 0.0001), septum neutrophils (2.0 [1.0–4.0]vs . 5.0 [3.3–6.0];p = 0.0008), necrotizing vasculitis (3.0 [2.0–5.5]vs . 6.0 [6.0–6.0];p = 0.0003), and ultrastructural lung damage scores (16 [14–17]vs . 24 [14–27], p < 0.0001). Blood colony-forming-unit (CFU) counts were comparable (7 [0–28]vs . 6 [0–26], p = 0.77). Compared to NV, VCV, but not VV, increased expression amphiregulin, IL-6, and cytokine-induced neutrophil chemoattractant (CINC)-1 (2.1 [1.6–2.5]vs . 0.9 [0.7–1.2], p = 0.025; 12.3 [7.9–22.0]vs . 0.8 [0.6–1.9], p = 0.006; and 4.4 [2.9–5.6]vs . 0.9 [0.8–1.4], p = 0.003, respectively). Angiopoietin-2 expression was lower in VV compared to NV animals (0.5 [0.3–0.8]vs . 1.3 [1.0–1.5], p = 0.01). Conclusion In this rat model of pneumonia, VV improved pulmonary function and reduced lung damage as compared to VCV, without increasing bacterial translocation.